Transparent zinc silicate/ zinc oxide crystallized glass-ceramics for water remediation application under visible light. Issue 7 (1st April 2023) - Yao, Ruijuan; Zhang, Ruiyin; Lang, Tingting; Zhou, Yang; Shi, Yongwen; Ma, Cheng; He, Zemin
Abstract: The present study focuses on taking advantage of both Zinc Silicate (Zn2 SiO4 ) and Zinc Oxide (ZnO) crystals in the glass matrix for enhancing photocatalytic activity. The fabricated samples were used as a photocatalyst for degrading ∼ 5 mg/L concentrated " Methylene Blue " (MB) and " Rhodamine B " (RB) dye separately under visible light. For this, 44 SiO2 :11 Al2 O3 :35 ZnO:10 K2 O compositions were prepared via the traditional melt quench process followed by heat treating at a temperature of 750 °C at 2, 4, and 6 h. Scanning electron microscopy (SEM), X-ray diffraction (XRD), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS) was employed to characterize the fabricated samples. The bandgap measured from Differential reflectance spectroscopy (DRS) was found to decrease with an increase in the heat treatment duration. 44 SiO2 :11 Al2 O3 :35 ZnO:10 K2 O composition heat-treated at 750 °C for 2 h degraded ∼59% and ∼71% of Rhodamine B (RB) dye and Methylene Blue (MB) dye under visible light in 4 h.